A lamellar full-dimensional perovskite single crystal and its preparation method and application

By instilting the perovskite precursor solution on a hydrophobic substrate and self-assembly using the interface on the top of the droplets, high-quality sheet-shaped full-dimensional perovskite single crystals were successfully prepared, solving the problems of insufficient stability and long preparation time in the prior art, and achieving single crystal synthesis with excellent photoelectric performance.

CN116200801BActive Publication Date: 2025-02-28FUDAN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310100468.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-12
Publication Date
2025-02-28
Estimated Expiration
2043-02-12

AI Technical Summary

Technical Problem

The existing perovskite single crystal preparation methods have problems such as insufficient stability, long preparation time, and limited application scope, and lack a high universal preparation method.

Method used

By preparing a perovskite precursor solution, it drops onto a hydrophobic substrate to form a growth micro-zone, and self-assembles using the interface between the solution on the top of the droplet and the air to control the growth time, and prepare a sheet-like full-dimensional perovskite single crystal.

Benefits of technology

The preparation of sheet-shaped full-dimensional perovskite single crystal with high quality and excellent photoelectric properties has been achieved, and the problems of insufficient stability and long preparation time in the prior art are overcome, and are suitable for high-quality single crystal synthesis in various structural dimensions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116200801B_ABST
    Figure CN116200801B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of semiconductor optoelectronic materials, specifically a sheet-like full-dimensional perovskite single crystal and its preparation method and application. The method of the present invention comprises: preparing a perovskite precursor solution and keeping it warm; dripping a trace amount of the perovskite precursor solution onto a hydrophobic substrate; self-assembling at the solution-air interface, controlling the growth time to complete the crystal growth; and preparing a perovskite single crystal with full structural dimensions according to different raw materials. The present invention utilizes octadecyltrichlorosilane to increase the surface tension of the droplets. Compared with the planar droplets, the curved droplets promote the anisotropic growth of low-dimensional and even three-dimensional perovskites. The present invention overcomes the problems of low aspect ratio of existing low-temperature grown single crystals and inability to be used in planar optoelectronic devices, and the preparation process is simple and efficient; the obtained single crystal has the characteristics of high quality, high aspect ratio, etc., emits symmetrical fluorescence peaks at room temperature, and has excellent optoelectronic properties; it can be widely used in the field of photoelectric detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor optoelectronic materials, and specifically relates to a lamellar full-dimensional perovskite single crystal and a preparation method and application thereof. Background Art

[0002] Photovoltaic technology is an important aspect of new energy technology. Perovskite materials are widely used in the field of photovoltaic technology due to their excellent photoelectric properties. At present, most of the research on perovskites is focused on polycrystalline thin films, and the lack of stability of polycrystalline is the biggest constraint restricting its application and development. Compared with polycrystalline, the intrinsic structural advantage of perovskite single crystals can solve the problem of stability attenuation from the root, and has many advantages such as higher carrier mobility, longer carrier lifetime, and lower grain boundary and defect density. In recent years, the preparation methods of perovskite single crystals mainly include slow solution cooling method, reverse temperature crystallization method, anti-solvent vapor assisted crystallization method, space confinement method, ultrasonic cavitation asymmetric crystallization method, top-down method and vapor phase epitaxy method. These methods have obvious advantages and disadvantages, and each has certain shortcomings. At present, there is still a lack of a universal method for preparing perovskite single crystals.

[0003] Chinese patent application CN110552061A discloses a method for growing perovskite single crystals by liquid phase diffusion separation crystallization at room temperature, which mainly includes two stages: introducing an exogenous solvent to seal the precursor mother solution and liquid phase diffusion to induce supersaturated crystallization of the solution. In the liquid sealing stage, the exogenous solvent forms a liquid seal protection for the precursor solution due to its different polarity from the endogenous solvent (mutually insoluble). In the crystallization stage, since the density of the exogenous solvent is less than that of the mother solution but greater than that of the endogenous solvent, the endogenous solvent will diffuse to the top layer so that the mother solution is continuously in a supersaturated state, thereby inducing the mother solution to precipitate crystal nuclei and grow to obtain large-sized single crystals. However, the above method is only applicable to the synthesis of bulk (i.e., block) single crystals. The ingenious density dependence is also difficult to extend to inorganic solvent systems. In addition, the growth process of this method is slow, and the separation and extraction process requires the material to grow to a macroscopic scale, which often takes several days to complete. Summary of the invention

[0004] The object of the present invention is to provide a lamellar full-dimensional perovskite single crystal with high material quality and excellent photoelectric performance, as well as a preparation method and application thereof.

[0005] The method for preparing a flaky full-dimensional perovskite single crystal provided by the present invention comprises the following specific steps:

[0006] (1) Prepare the perovskite precursor solution and keep it warm;

[0007] (2) taking a small amount of the perovskite precursor solution in step (1) and dropping it onto a hydrophobic substrate to form a perovskite single crystal growth microregion; the growth microregion is the interface between the solution at the top of the droplet and the air;

[0008] (3) The precursor solution self-assembles in the growth micro-area, i.e., at the interface between the solution and the air, and the growth time is controlled to complete the crystal growth, resulting in a lamellar full-dimensional perovskite single crystal.

[0009] The preparation method of the perovskite precursor solution in step (1) is as follows: dissolving the metal halide raw material of the perovskite in a solvent, and heating and stirring until it is completely dissolved.

[0010] The metal halide raw material is selected from cesium iodide, cesium bromide, lead iodide, lead bromide, bismuth iodide and antimony iodide.

[0011] The solvent is a saturated aqueous solution of a hydrohalic acid, and the hydrohalic acid is selected from hydroiodic acid and hydrobromic acid.

[0012] Preferably, the insulation temperature is 65-75°C.

[0013] Preferably, the microamount in step (2) is 3-5 μL.

[0014] Preferably, the hydrophobic substrate in step (2) is a clean glass slide that has been hydrophobically treated.

[0015] The hydrophobic treatment method is to soak the slide in a mixed solution of n-hexane and octadecyltrichlorosilane, wherein the volume ratio of n-hexane to octadecyltrichlorosilane is (400-600):1, and the soaking time is 1.5-2.5 h.

[0016] Preferably, the solution-air interface is the top region of the droplet.

[0017] Preferably, the growth time in step (3) is 3 to 10 s.

[0018] The present invention provides a perovskite single crystal prepared by the above method, which has a sheet structure, that is, the single crystal diameter is 30-200 μm and the thickness is 0.3-9.6 μm. It is different from the fast-shaped perovskite, and the diameter size is much larger than the thickness size.

[0019] The single crystals include full-dimensional perovskite single crystals of low-dimensional structures (0D, 1D and 2D) and three-dimensional structures (3D).

[0020] The present invention selects an inorganic solvent hydrogen halide aqueous solution as a crystal growth medium. In an aqueous medium, the solubility of the perovskite material decreases as the temperature decreases. A trace amount of solution is dripped onto a hydrophobic substrate through a heat-insulated precursor solution, and the droplets become supersaturated after cooling. Under the effect of the curved droplet enhancing the surface tension, nucleation and anisotropic crystal growth occur spontaneously at the liquid-air interface at the top of the droplet. In addition to the above effects, appropriately heating the droplets can accelerate the solvent evaporation rate, further induce supersaturated crystallization of the droplets, and increase the crystallization rate.

[0021] The present invention also includes the use of the above-mentioned perovskite single crystal in a photoelectric detector.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention uses a hydrohalic acid aqueous solution as a solvent. Different from most organic solvents such as dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and γ-butyrolactone (GBL), etc. (which are harmful to the human body after volatilization and also cause environmental pollution), the aqueous medium is more suitable for preparing single crystals as an environmentally friendly green solvent, and the perovskite single crystal synthesized in the aqueous system has better moisture resistance than that of the organic solvent system;

[0024] (2) The present invention seals the precursor solution and keeps it at a constant temperature, and uses a hydrophobic substrate to increase the contact angle to form a curved droplet, thereby enhancing the surface tension and promoting the anisotropic growth of crystals in the top area of ​​the liquid-air interface. This method can be used as a general simple crystallization method, suitable for synthesizing high-quality perovskite single crystals of various structural dimensions. The present invention overcomes the existing problems of low-temperature growth, low aspect ratio and inability to be used in planar optoelectronic devices. The method of the present invention adopts mild room temperature synthesis conditions, is simple and fast, has high preparation efficiency and good reliability, and the low concentration solution is conducive to reducing costs and improving raw material utilization;

[0025] (3) The perovskite single crystal prepared by the method of the present invention has a lamellar structure, that is, the single crystal diameter is 30-200 μm and the thickness is 0.3-9.6 μm. It has high quality, good morphology, uniform grain size, large aspect ratio, uniform element distribution, pure phase, and emits symmetrical fluorescence peaks at room temperature; it is applied to photodetectors, has excellent photoelectric performance, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 These are optical microscope images of the obtained perovskite single crystals. Among them, a) is a zero-dimensional structure single crystal Cs3Bi2I9, b) is a one-dimensional structure single crystal CsPbI3, c) is a two-dimensional structure single crystal Cs3Sb2I9, and d) is a three-dimensional structure single crystal CsPbBr3.

[0027] Figure 2 The photoluminescence (PL) curves of the obtained perovskite single crystals are shown in Figure 1. Among them, a) is the PL curve of the zero-dimensional structure single crystal Cs3Bi2I9, b) is the PL curve of the one-dimensional structure single crystal CsPbI3, c) is the PL curve of the two-dimensional structure single crystal Cs3Sb2I9, and d) is the PL curve of the three-dimensional structure single crystal CsPbBr3.

[0028] Figure 3 This is the scanning electron microscope (SEM) image of the obtained two-dimensional structured perovskite single crystal Cs3Sb2I9 and the corresponding element distribution map.

[0029] Figure 4 This is the X-ray photoelectron spectrum (XPS) diagram of the obtained two-dimensional structure perovskite single crystal Cs3Sb2I9.

[0030] Figure 5 This is the X-ray diffraction (XRD) pattern of the obtained three-dimensional perovskite single crystal CsPbBr3.

[0031] Figure 6 This is the IV curve of the planar photodetector based on the three-dimensional perovskite single crystal CsPbBr3. Implementation

[0032] The present invention will be further described below in conjunction with specific embodiments and drawings, but the embodiments do not limit the present invention.

[0033] Example 1, preparation of zero-dimensional structure Cs3Bi2I9 single crystal, the specific steps are as follows:

[0034] Step 1, adding cesium iodide and bismuth iodide (CsI, BiI3) in a molar ratio of 3:2 to a 55.0%-58.0% aqueous solution of hydroiodic acid, stirring and dissolving at 130°C to prepare a 0.015 mol / L clear precursor solution, and storing it in a 70°C constant temperature drying oven;

[0035] Step 2, take out the glass bottle containing the precursor solution from the constant temperature drying oven, and use a pipette to draw 3 μL of the precursor solution onto a dry, clean, hydrophobic glass slide substrate;

[0036] Step 3, cool the glass slide containing the droplet at room temperature for 3 seconds, and obtain a zero-dimensional structure Cs3Bi2I9 single crystal on the top of the curved droplet liquid-air interface.

[0037] Figure 1 a) is the optical image and thickness data of the obtained zero-dimensional structure Cs3Bi2I9 single crystal. The inset shows that the obtained single crystal has a diameter of about 30μm, a thickness of about 4.5μm, and an aspect ratio of 7.

[0038] Example 2, preparation of one-dimensional structure CsPbI3 single crystal, the specific steps are as follows:

[0039] Step 1, adding cesium iodide and lead iodide (CsI, PbI2) in a molar ratio of 1:1 to a 55.0%-58.0% aqueous solution of hydroiodic acid, stirring and dissolving at 130°C to prepare a 0.1 mol / L clear precursor solution, which is stored in a 70°C constant temperature drying oven;

[0040] Step 2, take out the glass bottle containing the precursor solution from the constant temperature drying oven, and use a pipette to draw 3 μL of the precursor solution onto a dry, clean, hydrophobic glass slide substrate;

[0041] Step 3, cooling the glass slide containing the droplet at room temperature for 3 seconds, and obtaining a one-dimensional structured CsPbI3 single crystal on the top of the curved droplet liquid-air interface.

[0042] Figure 1 b) is the optical image and thickness data of the obtained one-dimensional structured CsPbI3 single crystal. The inset shows that the obtained single crystal is about 200μm long, about 0.3μm thick, and has an aspect ratio of 667.

[0043] Example 3, preparation of two-dimensional structure Cs3Sb2I9 single crystal, the specific steps are:

[0044] Step 1, adding cesium iodide and antimony iodide (CsI, SbI3) in a molar ratio of 3:2 to a 55.0%-58.0% aqueous solution of hydroiodic acid, stirring and dissolving at 130°C to prepare a 0.008 mol / L clear precursor solution, which is stored in a 70°C constant temperature drying oven;

[0045] Step 2, take out the glass bottle containing the precursor solution from the constant temperature drying oven, and use a pipette to draw 3 μL of the precursor solution onto a dry, clean, hydrophobic glass slide substrate;

[0046] Step 3, cool the glass slide containing the droplet at room temperature for 5 seconds, and obtain a two-dimensional structure Cs3Sb2I9 single crystal on the top of the curved droplet liquid-air interface.

[0047] Figure 1 c) is the optical image and thickness data of the obtained two-dimensional structure Cs3Sb2I9 single crystal. The inset shows that the obtained single crystal has a diameter of about 75 μm, a thickness of about 1.7 μm, and an aspect ratio of 44.

[0048] Figure 3 The SEM image and corresponding element distribution map of the obtained two-dimensional structure Cs3Sb2I9 single crystal show that the obtained single crystal has good crystal morphology and uniform element distribution.

[0049] Figure 4 This is the XPS image of the obtained two-dimensional structure Cs3Sb2I9 single crystal, showing the elemental composition and elemental compound state of the obtained single crystal.

[0050] Example 4, preparation of three-dimensional structure CsPbBr3 single crystal, the specific steps are:

[0051] Step 1, adding cesium bromide and lead bromide (CsBr, PbBr2) in a molar ratio of 1:1 to a 55.0%-58.0% hydrobromic acid aqueous solution, stirring and dissolving at 130°C to prepare a 0.1 mol / L clear precursor solution, and storing it in a 70°C constant temperature drying oven;

[0052] Step 2, take out the glass bottle containing the precursor solution from the constant temperature drying oven, and use a pipette to draw 3 μL of the precursor solution onto a dry, clean, hydrophobic glass slide substrate;

[0053] Step 3: Place the glass slide containing the droplet on a 50 °C hot plate to cool for 10 s, and obtain a three-dimensional CsPbBr3 single crystal on the top of the curved droplet liquid-air interface.

[0054] Figure 1 d) is the optical image and thickness data of the obtained three-dimensional structured CsPbBr3 single crystal. The inset shows that the obtained single crystal is about 100 μm long, about 9.6 μm thick, and has an aspect ratio of 10.

[0055] Figure 5 This is the XRD diagram of the obtained three-dimensional structure perovskite single crystal CsPbBr3, which shows that the phase composition of the obtained single crystal is consistent with the standard spectrum.

[0056] Figure 6 This is the IV curve of the planar photodetector based on the three-dimensional perovskite single crystal CsPbBr3. The test results show that under a bias of 3 V, the photocurrent is as high as 0.1 μA, the dark current is as low as 100 pA, and the switching ratio reaches more than three orders of magnitude, showing excellent photoelectric performance.

[0057] The zero-dimensional structure Cs3Bi2I9 single crystal prepared in Example 1, the one-dimensional structure CsPbI3 single crystal prepared in Example 2, and the two-dimensional structure Cs3Sb2I9 single crystal prepared in Example 3 also have similar photoelectric properties.

[0058] This shows that the present invention is an effective method for preparing high-quality single crystals.

[0059] The above description is only a preferred specific implementation manner of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention should be included in the scope of protection of the invention.

Claims

1. A method for preparing a lamellar full-dimensional perovskite single crystal, characterized in that: The specific steps are: (1) Prepare the perovskite precursor solution and keep it warm; (2) taking a small amount of the perovskite precursor solution in step (1) and dropping it onto a hydrophobic substrate to form a perovskite single crystal growth microregion; the growth microregion is the interface between the solution at the top of the droplet and the air; the small amount is 3-5 μL; (3) The precursor solution self-assembles in the growth micro-region, i.e., at the interface between the solution and the air, and the growth time is controlled to complete the crystal growth to obtain a lamellar full-dimensional perovskite single crystal; the growth time is 3 to 10 s; The method for preparing the perovskite precursor solution in step (1) is as follows: dissolving the metal halide raw material of the perovskite in a solvent, heating and stirring until it is completely dissolved; The metal halide raw material is selected from cesium iodide, cesium bromide, lead iodide, lead bromide, bismuth iodide and antimony iodide; The solvent is a saturated aqueous solution of a hydrohalic acid, and the hydrohalic acid is selected from hydroiodic acid and hydrobromic acid.

2. The preparation method according to claim 1, characterized in that: The insulation temperature in step (1) is 65-75°C.

3. The preparation method according to claim 1, characterized in that: The hydrophobic substrate in step (2) is a clean glass slide that has been hydrophobically treated.

4. The preparation method according to claim 3, characterized in that: The hydrophobic treatment method in step (2) is to immerse the glass slide in a mixed solution of n-hexane and octadecyltrichlorosilane; wherein the volume ratio of n-hexane to octadecyltrichlorosilane is (400-600):1; and the immersion time is 1.5-2.5 h.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The sheet has a single crystal diameter of 30-200 μm and a thickness of 0.3-9.6 μm.

6. The preparation method according to claim 5, characterized in that: The full-dimensional perovskite single crystal is a perovskite single crystal including 0-dimensional, 1-dimensional, 2-dimensional and 3-dimensional structures.

Citation Information

Patent Citations

  • Method for preparing large-area organic-inorganic hybrid perovskite single crystal nanowire array

    CN106757370A

  • Zero-dimensional bismuth-based perovskite single-crystal material and preparation method and application thereof

    CN110230103A

  • Preparation method for growing perovskite single crystal by liquid-phase diffusion separation crystallization at room temperature

    CN110552061A

  • Method for preparing high-fluorescence zero-dimensional perovskite single crystal through solution self-assembly

    CN110735182A

  • Growth method of one-dimensional DMAPbI3 large single crystal

    CN112251815A